Trajectories of Operations Strategy: a longitudinal study at an auto engine factory in Brazil - Maia, Jonas Lucio; Cerra, Aline Lamon; Alves Fiho, Alceu Gomes; Oliveira, Gerusa Tinasi de (Revista Gestão da Produção Operações e Sistemas, 2010)
The Brazilian automotive industry has undergone a process of important changes over the past decades, such as the establishing of new automakers in the country, adoption of new relationship patterns and consolidation/ denationalization of auto suppliers. During the same period, literature on business strategies has seen the rise of a new set of ideas, which have become known as the “Resource Based View”, whose main contribution is em- phasizing the strategic importance of a resource that is costly to imitate, transfer, buy, sell or substitute, and that achieves systemic integration with all the other company’s resources. Considering that the development of such “strategic resources” takes place along specific trajectories, this paper aims at analyzing recent Operations Strategy (OS) trajectories followed by a car engine manufacturer set up in Brazil. Findings suggest that, within the context of the OS, priorities set at a specific point in time act as a translation of the “strategic intent” to be pursued in following periods, becoming a driver for coming strategy. Decisions made in each of the operational decision areas create unique, sequentially developed competencies that increase the company’s level of competitiveness. Keywords: Operations Strategy; Resource Based View; Competences; Automotive Industry; Automotive Engines.